Investigation of cultural dependency in mobile technology and older adults - Sofianiza, Abd Malik; Alistair, Edwards (2012)
Studies using different methods have been carried out of older adults’ use of mobile technology in Malaysia and the UK. Preliminary results suggest that there are significant differences in the results which are culturally dependent.